2016
DOI: 10.1186/s40697-016-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality on Continuous Renal Replacement Therapy (CRRT): The Prairie CRRT Study

Abstract: BackgroundPatients with acute kidney injury (AKI) requiring renal replacement therapy (RRT) have an increased short-term and long-term risk of mortality. In most North American intensive care units (ICUs), these patients receive continuous renal replacement therapy (CRRT).ObjectiveWe aim to identify clinical and demographic factors associated with mortality within 24 h of initiating CRRT.DesignThis paper is a prospective cohort study.SettingThe setting involves three ICUs (12-bed surgical ICU, 10-bed medical I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
2
25
1
Order By: Relevance
“…Although this mortality rate does not consider the number of patients excluded from mortality analysis (23 of 108) owing to liver transplant, it is near the range reported in large studies in the literature that have generally not included patients awaiting liver transplant. 9,[16][17][18] Few studies include patients in an SICU, and when included, these patients are rarely treated as a separate population. A notable exception is a study conducted by the National Taiwan University Surgical ICU Associated Renal Failure Study Group (NSARF) from 2002 to 2006, 19 which found a 40% rate of survival at 90 days after initiation of CRRT among 137 patients undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although this mortality rate does not consider the number of patients excluded from mortality analysis (23 of 108) owing to liver transplant, it is near the range reported in large studies in the literature that have generally not included patients awaiting liver transplant. 9,[16][17][18] Few studies include patients in an SICU, and when included, these patients are rarely treated as a separate population. A notable exception is a study conducted by the National Taiwan University Surgical ICU Associated Renal Failure Study Group (NSARF) from 2002 to 2006, 19 which found a 40% rate of survival at 90 days after initiation of CRRT among 137 patients undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, these models did not focus on patients initiating CRRT for AKI. A few studies have identified risk factors of mortality in patients receiving CRRT [29,30]. Nevertheless, it is necessary to develop a mortality prediction model because a few clinical variables may not be sufficient to precisely predict patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile it resulted in lung injury and gas exchange by inducing pulmonary inflammatory response. Tumor necrosis factorα and other immunomodulatory molecules were released as a response to the reaction of the infection [24,25].Prasad et al found that patients with a higher FiO2 requirements while ventilated and a higher vasoactive agent requirement were inclined to have an early(24 h) mortality [26]. PCP prophylaxis has been widely used in developed country [23], but still unpopularly used in developing country.…”
Section: Discussionmentioning
confidence: 99%